Towards Balanced Bicameralism: Reconstruction of Law-making powers in Indonesian Representative Institutions - Marzuki, Marzuki (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2022)
This study intends to analyze the problems of parliamentary institutions in Indonesia, with a focus on the inequality of authority between the first chamber (DPR) and the second chamber (DPD) in the lawmaking process. It also offers normative-conceptual ideas on the reconstruction formula for balancing the roles of both houses in the law-making power, according to the concept of balanced or strong bicameralism. The study uses a doctrinal legal research model, through a literature study of primary and secondary legal materials. This study also combines constitutional, theoretical, and statutory/normative approaches. The analysis is presented descriptively-prescriptively with qualitative techniques. The findings indicate that the authority of both chambers (DPD & DPR) in the law-making power, as regulated in the 1945 Constitution of the Republic of Indonesia and in statutory regulations, is still not proportional. This is due to the DPD's limited authority, both to submit a draft law and to discuss a bill that has not reached the final approval stage. In comparison to the DPR's unlimited authority, the DPD is still identified as a co-legislator or an auxiliary authority in the law making process. As a result, the relationship between the two chambers as representative institutions must be reconstructed on the basis of balanced bicameralism or strong bicameralism. Reconstruction efforts must be carried out by altering some provisions in the Constitution, and making adjustments to other regulations at the statutory level. It is hoped that the two chambers can synergize with each other and accommodate national and local aspirations to produce higher quality legal products.